Performance of Safety Sea Transportation - Faturachman, Danny; Shariman, Mustafa (Elsevier Ltd, 2012)
Indonesia is the world’s largest archipelago, 2/3 of the country is covered by sea. But due to many factors a lot of ship accidents occurred every year, and claiming a large number of casualties. Efforts have been done to improve the safety of domestic sea transportation, as the result to be fully compliance to the SOLAS regulations, worsen by the varying sea and cargo characteristics, and low educated passengers, they are very vulnerable to accidents. . Most of the accidents occur due to the low awareness of the aspects of security and safety of the crew. The figures differ from the manifest of passengers and number of passengers on the ground become commonplace. There are four main issues in maritime transport, it is said, not the individual agencies or Government willing to hold responsibility for the security and safety, pricing policy, the quality of human resources, as well as the implementation and compliance with the rules are not clear